Alternatives to Lean Production : Work Organization in the Swedish Auto Industry - Berggren, Christian (Cornell International Industrial and Labor Relations Reports, 2019)
The Swedish auto industry has developed a distinct production design and work organization, exploring alternatives to the assembly line and to the traditional shop-floor hierarchy, with a model of teamwork that increases independent decision making and elicits strong union commitment. Berggren evaluates in detail the reorganization of work within the Swedish auto industry from 1970 to 1990. In his introduction to the new edition, he explores the significance of Volvo's decision to close its two most innovative plants.